Utility of a targeted next-generation sequencing-based genetic screening panel in patients with periodic fever, aphthous stomatitis, pharyngitis, and adenitis syndrome - Rabia Miray Kışla Ekinci; Özlem Anlaş; Özge Özalp (Archives of Rheumatology, 2023)
Objectives: This study aims to investigate a genetic panel in patients with periodic fever, aphthous stomatitis, pharyngitis, and adenitis (PFAPA) syndrome and examine its performance for an accurate differential diagnosis. Patients and methods: Between January 2021 and January 2022, a total of 104 children with PFAPA syndrome (63 males, 41 females; mean age: 4.8±2.3 years; range, 1.2 to 8.9 years) were retrospectively analyzed. Next-generation sequencing test was performed using a custom QIAGEN- QIAseq™ Targeted DNA Panel which includes six genes namely ELANE, LPIN2, MEFV, MVK, NLRP3, and TNFRSF1A. Results: Of 104 patients, 38 (36.5%) had variants in the genetic panel. The most common variants were found in the MEFV gene (n=35, 33.6%), the most frequent genotype was E148Q heterozygosity (n=16). Four and two patients were eventually diagnosed with Familial Mediterranean fever (FMF) and hyperimmunoglobulin D syndrome (HIDS), since they had confirmative biallelic pathogenic in the MEFV and MVK genes, respectively. Conclusion: A genetic panel, including MEFV and MVK genes, may be useful in patients, clinically resembling PFAPA, since they may have HIDS or FMF, but lack typical features of the exact disease. Nonetheless, we believe that distinct genetic panels should be developed for different populations.